(untitled) (Sudurpaschim Spectrum, 2023)
This paper excavates the valorization of violence in Chinua Achebe’s Things Fall Apart through the anthropological perspective of violence. Things Fall Apart explores the pre-colonial Igbo land of Umuofia, Nigeria. The Umuofian culture glorifies the violence very highly and people of Umuofia even legitimize the homicide in the name of masculinity. Their cultural practices encourage not only inter-cultural clash and conflict but intra-cultural violence between and among its members. The protagonist of the novel, Okonkwo, is a respected warrior and clan leader of Umuofia. He frequently exhibits violent acts: he kills a fifteen-year-old boy Ikemefuna to prove his masculinity; at Ezeudu’s funeral, Okonkwo’s gun explodes and kills Ezeudu’s son; he then slaughters a court messenger and finally commits suicide. Furthermore, Okonkwo kills several people in inter-racial wars. He severely beats his wives and children; he often quarrels with neighbors and engages himself in fierce wrestling matches. Umuofians’ associate violence with manliness and if a man fails to perform it, he is considered a woman. The present reading thus, attempts to unveil violence and its glorification in the name of culture, masculinity, ritual sacrifice, and other kinds of communally sanctioned violence.